Structural Characterization of N‐Linked Glycans in the Receptor Binding Domain of the SARS‐CoV‐2 Spike Protein and their Interactions with Human Lectins. Issue 52 (22nd October 2020) - Lenza, Maria Pia; Oyenarte, Iker; Diercks, Tammo; Quintana, Jon Imanol; Gimeno, Ana; Coelho, Helena; Diniz, Ana; Peccati, Francesca; Delgado, Sandra; Bosch, Alexandre; Valle, Mikel; Millet, Oscar; et al.
Abstract: The glycan structures of the receptor binding domain of the SARS‐CoV2 spike glycoprotein expressed in human HEK293F cells have been studied by using NMR. The different possible interacting epitopes have been deeply analysed and characterized, providing evidence of the presence of glycan structures not found in previous MS‐based analyses. The interaction of the RBD 13 C‐labelled glycans with different human lectins, which are expressed in different organs and tissues that may be affected during the infection process, has also been evaluated by NMR. In particular, 15 N‐labelled galectins (galectins‐3, ‐7 and ‐8 N‐terminal), Siglecs (Siglec‐8, Siglec‐10), and C‐type lectins (DC‐SIGN, MGL) have been employed. Complementary experiments from the glycoprotein perspective or from the lectin's point of view have permitted to disentangle the specific interacting epitopes in each case. Based on these findings, 3D models of the interacting complexes have been proposed. Abstract : Unprecedent structural details of the glycans of the RBD of SARS‐CoV‐2 spike glycoprotein have been revealed by NMR spectroscopy. Unexpected and non‐previously reported glycoepitopes have been detected. The interaction of the RBD glycoprotein with diverse human lectins has been scrutinised by exploiting the NMR signature of the 13 C‐glycans. Our analysis permitted to identify the corresponding glycan epitopes responsible for the interaction with each lectin.